Promotion of breastfeeding in Italian Maternity Hospitals: a pre-intervention study - Riccardo Davanzo; Guglielmo Salvatori; Mariella Baldassarre; Irene Cetin; Elsa Viora; Elena Scarpato; on behalf of the "HPB Project" Working Group (BMC, 2024)
Abstract Background In Italy, exclusive breastfeeding (EBF) rates at hospital discharge range unsatisfactorily between 20-97%. Methods In 2023, the Project for Hospital Policy on Breastfeeding (HPB) has been launched to promote breastfeeding in Italian Maternity Hospitals (MHs) as a joint initiative of the Italian Scientific Societies involved in perinatal care together with the National Midwife (FNOPO) and Nurse (FNOPI) Boards and with Vivere Onlus, a family association. The HBP Project has been designed as an uncontrolled before-after study to increase EBF rate at hospital discharge in the population of healthy, term infant with a normal weight at birth following an intervention bundle comprising: 1) Establishment of a local hospital Working Group; 2) Adoption of a hospital policy; 3) Implementation of breastfeeding monitoring; 4) Training for perinatal care professionals; 5) Enhanced implementation of the practices of skin-to-skin contact (SSC) and mother-baby rooming-in; 6) Development/Improvement of perinatal care protocols. Results We report the pre-intervention assessment of 89 out of the 111 enrolled MHs (80.2%) at the beginning of the Project (Time 1 or T1). Almost all MHs (96.6%) have a multi-professional Breastfeeding Working Group, while a hospital policy on breastfeeding is available only in 48.2%. Moreover, only 56.2% of the 9,777 perinatal health workers have been trained in breastfeeding. Over a 1-month period, SSC has been practiced in the delivery room by 76.9% of 6,304 term healthy newborn infants and rooming-in by 83.4% of 6,735 healthy term newborns of normal weight at birth. Over a 4-month period, 69.1% of 33,367 healthy term newborns of normal birth weight were exclusively breastfed at hospital discharge. Noticeably, EBF rate of MHs ranges from 4% up to 100%, the second quartile being 73%. Conclusion At T1 of the HPB Project, breastfeeding rates at hospital discharge for healthy, term infants with a normal weight at birth appear to be suboptimal among Italians MHs. Particularly, the range of EBF rates among participating centers is wide, with 50% of the MHs having EBF rate lower than 73%. Therefore, the ongoing HPB Project might represent not only an opportunity to increase the initiation of breastfeeding and to improve quality of health care in the whole study group of MHs, but possibly also to level differences between centers.